The Interleukin-20 Cytokine Family in Liver Disease - Caparrós, Esther; Francés, Rubén (Frontiers in Immunology, 2018)
The three main causes of inflammation and chronic injury in the liver are viral hepatitis, alcohol consumption, and non-alcoholic steatohepatitis, all of which can lead to liver fibrosis, cirrhosis, and hepatocellular carcinoma, which in turn may prompt the need for liver transplant. The interleukin (IL)-20 is a subfamily part of the IL-10 family of cytokines that helps the liver respond to damage and disease, they participate in the control of tissue homeostasis, and in the immunological responses developed in this organ. The best-studied member of the family in inflammatory balance of the liver is the IL-22 cytokine, which on the one hand may have a protective role in fibrosis progression but on the other may induce liver tissue susceptibility in hepatocellular carcinoma development. Other members of the family might also carry out this dual function, as some of them share interleukin receptor subunits and signal through common intracellular pathways. Investigators are starting to consider the potential for targeting IL-20 subfamily members in liver disease. The recently explored role of miRNA in the transcriptional regulation of IL-22 and IL-24 opens the door to promising new approaches for controlling the local immune response and limiting organ injury. The IL-20RA cytokine receptor has also been classified as being under miRNA control in non-alcoholic steatohepatitis. Moreover, researchers have proposed combining anti-inflammatory drugs with IL-22 as a hepatoprotective interleukin for alcoholic liver disease treatment, and clinical trials of interleukins for managing severe alcoholic-derived liver degeneration are ongoing. In this review, we focus on exploring the role of the IL-20 subfamily of cytokines in viral hepatitis, alcoholic liver disease, non-alcoholic steatohepatitis and hepatocellular carcinoma, as well as delineating the main strategies explored so far in terms of therapeutic possibilities of the IL-20 subfamily of cytokines in liver disease.